Edukasi dan pemanfaatan Aplikasi Buku kas Dalam pengelolaan keuangan pada Usaha UMKM Faeyza Laundry di Kota bengkulu - Fitriano, Yun; Sari, Nely Puspita; Amelya, Tifani Rika; Lutfiani, Irma (Jurnal Dehasen Mengabdi, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the most numerous types of businesses in Indonesia. One of them is the Faeyza Laundry Business which is located on Jalan Sumatra Sukamerindu, Bengkulu city, the Faeyza Laundry business is one of the MSMEs engaged in the laundry of clothes. Based on the results of a previous survey with Faeyza Laundry business owners, it is known that this Laundry business has not prepared financial reports, this is due to a lack of knowledge and information about financial reports. Then the recording of financial reports in the Faeyza Laundry business is also still very simple, by manually recording incoming and outgoing cash every day. Based on these problems, we aim to help business owners by providing education and training regarding the use of the Cash Book Application in managing their finances.